RESEARCH ACTIVITIES AT KURSK STATE MEDICAL UNIVERSITY - Pavel V. Kalutsky (Moscow Polytechnic University, 2016)
The basis of the article is an analysis of the research activities of students and staff of Kursk State Medical University. The article touches on the principles of organization and the effectiveness indeces of the research work of students, young scientists and faculty members of the University. Gives the basic characteristic of infrastructure aimed at implementation of innovative research projects, interaction with business community, the leading Russian and foreign universities and research centers. This infrastructure allows University to carry out productive research and innovative work on the priority areas of Russian economy and the Kursk region.